(untitled) (SCHOOLAR: Social and Literature Study in Education, 2024)
The objective of this research is to find out how the â€œDysKing (Dysarthria`s Speaking)â€ application can help dysarthria students in learning to speak. It is hoped that the results of this research can help teachers’ strategies in teaching speaking skill through â€œDysKing (Dysarthria`s Speaking)â€ especially for students with dysarthria. This research involved 4 dysarthria students at SMPLB Tunas Harapan I Tembelang Jombang in the Academic Year 2022/2023. This research uses the R&D research and development method with the ADDIE research model (Analysis, Design, Development, Implementation, Evaluation). This research was conducted at SMPLB Tunas Harapan 1 Tembelang Jombang. Data were collected through qualitative data. The researcher analyzed based on the results of observations and interviews. The results of this research show that the result of media validation got 4.46 score which was in the â€œgoodâ€ category, and the result of material validation got 4.19 score. The result of students` responses got 4.3 score is was â€œgoodâ€ category. With these results, "DysKing (Dysarthria`s Speaking)" is suitable to be used as learning media for dysarthria students. In addition, this research can also be used as a reference for other researchers in developing English learning media for different student levels.